Fine-grain zinc sheet with preferred orientation, preparation method of fine-grain zinc sheet and application of fine-grain zinc sheet in aqueous zinc ion battery

By annealing and high-pressure torsion treatment on the zinc sheet, its microstructure is changed, and the zinc dendrites caused by uneven deposition of zinc ions in aqueous zinc ion batteries are solved, which significantly improves the performance and life of the battery.

CN119800258APending Publication Date: 2025-04-11SHANGHAI UNIV OF ENG SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510074810.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the charging and discharging process of aqueous zinc ion batteries, uneven deposition of zinc ions leads to zinc dendrites, piercing the separator and contacting the positive electrode, resulting in internal short circuits and shortening of battery life.

Method used

By annealing the zinc sheet and high-pressure torsion (HPT) treatment, the microstructure of the zinc sheet is changed to show the (002) crystal plane orientation and reduce the grain size.

Benefits of technology

It effectively overcomes the defects of zinc dendrites, passivation and corrosion, improves the capacity, cycle stability and rate performance of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800258A_ABST
    Figure CN119800258A_ABST
Patent Text Reader

Abstract

The invention discloses a fine-grain zinc sheet with preferred orientation, a preparation method of the fine-grain zinc sheet and application of the fine-grain zinc sheet in an aqueous zinc ion battery. And the fine-grain zinc sheet is obtained by sequentially carrying out annealing treatment and high-pressure torsion treatment on a zinc sheet. The zinc sheet is sequentially subjected to annealing treatment and high-pressure torsion treatment, the microstructure of the zinc sheet is changed, the treated zinc sheet presents (002) crystal face preferred orientation, the grain size is reduced, and the grain size of the zinc sheet is reduced to 20 micrometers from 1000 micrometers or above, and when the treated zinc sheet is used as the negative electrode of the zinc ion battery, the grain size of the zinc sheet is reduced to 20 micrometers from 1000 micrometers or above. The defects of zinc dendrite, passivation and corrosion are effectively overcome, and the battery has higher battery capacity, higher cycling stability and higher rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fine-crystalline zinc sheet with preferred orientation, a preparation method thereof and application in an aqueous zinc ion battery, belonging to the technical field of aqueous zinc ion batteries. Background Art

[0002] With the widespread adoption of electric vehicles, renewable energy systems, and portable electronic devices, the global demand for efficient, sustainable, and safe batteries is rising. While lithium-ion batteries have surpassed nickel-metal hydride batteries and dominated the battery market, concerns about lithium resource scarcity, safety, and environmental impact have prompted the search for alternative battery chemistries. Zinc-based batteries are a viable alternative due to their abundant zinc resources, low cost, and non-toxic properties.

[0003] Zinc-based batteries can be roughly divided into two categories: zinc-air batteries and aqueous zinc-ion batteries. Zinc-air batteries generate electricity by reacting zinc with oxygen in the air. Aqueous zinc-ion batteries work by inserting and deintercalating zinc ions into host materials, usually in a closed system. Zinc-air batteries are limited by challenges such as their dependence on atmospheric oxygen and sensitivity to carbon dioxide. Aqueous zinc-ion batteries can provide a more stable and controllable electrochemical process with a longer cycle life and higher power output. Therefore, aqueous zinc-ion batteries have become a research hotspot for zinc-based batteries.

[0004] Aqueous zinc-ion batteries are usually composed of a positive electrode, a negative electrode, an electrolyte, a separator, etc. The negative electrode material is the key factor that determines the performance of aqueous zinc-ion batteries. At present, the negative electrode material of aqueous zinc-ion batteries is zinc. However, during the charge and discharge process of aqueous zinc-ion batteries, zinc ions will be unevenly deposited on the zinc negative electrode, causing zinc dendrites to appear on the negative electrode of the battery, piercing the separator and contacting the positive electrode, causing the battery to fail due to internal short circuit, shortening the battery life. In addition, the passivation and corrosion of zinc will also hinder the electrochemical performance of the negative electrode, thereby reducing the ion transmission efficiency, increasing polarization, reducing the overall performance of the battery, and shortening the battery life. Summary of the invention

[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide a fine-crystalline zinc sheet with preferred orientation, a preparation method thereof and an application thereof in an aqueous zinc ion battery.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0007] A fine-grained zinc sheet with preferred orientation is obtained by successively subjecting the zinc sheet to annealing treatment and high pressure torsion (HPT) treatment.

[0008] A method for preparing fine-crystalline zinc flakes with preferred orientation according to the present invention comprises the following steps:

[0009] a) annealing the clean zinc sheet at 520K to 530K for 1 to 1.5 hours to obtain an annealed zinc sheet;

[0010] b) The annealed zinc sheet is subjected to a high-pressure torsion treatment, wherein the pressure of the high-pressure torsion is 5 to 10 GPa, the rotation speed is 1 to 2 rpm, and the number of revolutions is 9 to 11, so as to obtain a fine-grained zinc sheet with a preferred orientation.

[0011] The invention discloses an application of a fine-crystalline zinc sheet with preferred orientation in an aqueous zinc ion battery, and the fine-crystalline zinc sheet is used as a negative electrode of the aqueous zinc ion battery.

[0012] In one implementation scheme, the upper and lower surfaces of the fine-crystalline zinc sheet are first polished, and the sheet is polished to a thickness suitable for a negative electrode sheet of an aqueous zinc ion battery and then used as the negative electrode of the zinc ion battery.

[0013] In one implementation, sandpaper is used to grind the upper and lower surfaces of the fine-crystalline zinc sheet, specifically: sandpapers with mesh sizes of 360, 800, 1000, 1500, 2000, 2500, 3000, and 5000 are used in sequence to grind the upper and lower surfaces of the fine-crystalline zinc sheet.

[0014] A preferred solution is to grind the fine-crystalline zinc sheet to a thickness of 0.5 to 0.7 mm.

[0015] An aqueous zinc ion battery comprises a positive electrode and a negative electrode, a separator arranged between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is VO 2 The positive electrode and the negative electrode are the above-mentioned fine-grained zinc sheets with preferred orientation, and the electrolyte is 3M Zn(CF 3 SO 3 ) 2 Aqueous solution, the diaphragm is glass fiber.

[0016] In one embodiment, the aqueous zinc ion battery is a button battery.

[0017] Compared with the prior art, the present invention has the following significant beneficial effects:

[0018] The present invention sequentially performs annealing treatment and high-voltage torsion treatment on the zinc sheet, thereby changing the microstructure of the zinc sheet, making the treated zinc sheet present a (002) crystal plane preferential orientation, reducing the grain size, and reducing the grain size of the zinc sheet from more than 1000μm to 20μm. When the treated zinc sheet is used as the negative electrode of a zinc ion battery, it not only effectively overcomes the defects of zinc dendrites, passivation and corrosion, but also enables the battery to have a higher battery capacity, stronger cycle stability and rate performance. Compared with the prior art, the present invention not only produces unexpected technical effects, but also has significant advancement. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The metallographic micrographs are of the common zinc sheet (a) used in comparative example 1 of the present invention, the annealed zinc sheet (b) prepared in comparative example 2, and the fine-grained zinc sheet (c) prepared in example 1. The upper right corner of the picture is the corresponding optical photograph;

[0020] Figure 2 XRD spectra of the fine-crystalline zinc sheet (a) prepared in Example 1 of the present invention and the annealed zinc sheet (b) prepared in Comparative Example 2;

[0021] Figure 3 The SEM-EBSD spectra of the fine-crystalline zinc sheet (b) prepared in Example 1 of the present invention and the annealed zinc sheet (a) prepared in Comparative Example 2;

[0022] Figure 4 The cyclic voltammetry test diagrams of the zinc ion batteries using the zinc sheets prepared in Comparative Example 1, Comparative Example 2 and Example 1 as the negative electrode after being activated for two cycles at a current density of 0.05 A / g and then cycled for 50 cycles at 0.5 A / g; wherein line a is the cycle-coulomb efficiency curve of the annealed zinc negative electrode battery obtained by annealing without HPT treatment in Comparative Example 2, line b is the cycle-coulomb efficiency curve of the ordinary zinc negative electrode battery in Comparative Example 1, and line c is the cycle-coulomb efficiency curve of the fine-crystalline zinc negative electrode battery obtained by annealing first and then HPT treatment in Example 1 Cycle-Coulomb efficiency curve, line d is the cycle-capacity curve of the fine-crystalline zinc negative electrode battery in Example 1, line e is the cycle-capacity curve of the annealed zinc negative electrode battery in Example 2, and line f is the cycle-capacity curve of the ordinary zinc negative electrode battery in Example 1; line a and line e together are the constant current charge-discharge curve of the annealed zinc negative electrode battery in Example 2, line b and line f together are the constant current charge-discharge curve of the ordinary zinc negative electrode battery in Example 1, and line c and line d together are the constant current charge-discharge curve of the fine-crystalline zinc negative electrode battery in Example 1;

[0023] Figure 5The optical photographs and scanning electron microscope photographs of the fine-crystalline zinc sheet prepared in Example 1 of the present invention and the annealed zinc sheet prepared in Comparative Example 2 after 50 charge-discharge cycles, wherein (a) and (c) are respectively the optical photograph and scanning electron microscope photograph of the annealed zinc sheet after 50 charge-discharge cycles; (b) and (d) are respectively the optical photograph and scanning electron microscope photograph of the fine-crystalline zinc sheet after 50 charge-discharge cycles;

[0024] Figure 6 The cyclic voltammetry test graphs of zinc ion batteries using the zinc sheets prepared in Comparative Example 3, Comparative Example 4 and Example 5 as negative electrodes, after being activated for two cycles at a current density of 0.05 A / g and then cycling for 50 cycles at 0.5 A / g; wherein line a is the cycle-coulomb efficiency curve of the zinc negative electrode battery obtained by annealing first and then HPT treatment and HPT treatment (1 / 4 turn) in Comparative Example 5, line b is the cycle-coulomb efficiency curve of the zinc negative electrode battery obtained by HPT treatment first and then annealing in Example 4, line c is the cycle-coulomb efficiency curve of the zinc negative electrode battery obtained by HPT treatment only without annealing in Example 3, line d is the cycle-coulomb efficiency curve of the zinc negative electrode battery obtained by annealing first and then HPT treatment and HPT treatment in Example 5 The cycle-capacity curve of the zinc negative electrode battery obtained by annealing first and then HPT treatment in Example 5, the cycle-capacity curve of the zinc negative electrode battery obtained by annealing first and then HPT treatment (1 / 4 turn), the cycle-capacity curve of the zinc negative electrode battery obtained by HPT treatment only in Example 3, and the cycle-capacity curve of the zinc negative electrode battery obtained by HPT treatment only in Example 4; the constant current charge-discharge curve of the zinc negative electrode battery obtained by annealing first and then HPT treatment and HPT treatment (1 / 4 turn) in Example 5, the constant current charge-discharge curve of the zinc negative electrode battery obtained by HPT treatment first and then annealing in Example 4, and the constant current charge-discharge curve of the zinc negative electrode battery obtained by HPT treatment only in Example 3 without annealing are combined with the line a and line d. DETAILED DESCRIPTION

[0025] The technical scheme of the present invention is further described in detail and completely below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0026] Example 1

[0027] a) annealing a clean zinc sheet with a thickness of 1 mm at 523 K for 1 hour to obtain an annealed zinc sheet;

[0028] b) The annealed zinc sheet is subjected to high pressure torsion (HPT) treatment, with a pressure of 6 GPa, a rotation speed of 1 rpm, and a number of revolutions of 10, to obtain a fine-grained zinc sheet with a preferred orientation.

[0029] The upper and lower surfaces of the prepared fine-crystalline zinc sheet are polished with sandpaper of 360, 800, 1000, 1500, 2000, 2500, 3000 and 5000 meshes in sequence, and the thickness is polished to 0.5 mm, and the sheet is cut into a circular zinc sheet with a diameter of 10 mm, which can be used as the negative electrode of the zinc ion battery.

[0030] The zinc ion battery in this embodiment takes a button battery as an example, and its assembly is specifically as follows:

[0031] The negative electrode of the zinc ion battery is the fine-crystalline zinc sheet prepared in this example, and the positive electrode is VO 2 The positive electrode and electrolyte are 3M Zn(CF 3 SO 3 ) 2 The solution is glass fiber, the separator is glass fiber, the battery shell (including the positive electrode shell and the negative electrode shell) is a CR2032 type battery shell, and the button-type zinc ion battery is assembled in the order of "positive electrode shell-positive electrode sheet-electrolyte-glass fiber separator-HPT / annealed zinc negative electrode sheet-gasket-spring-negative electrode shell" using the existing button battery assembly technology.

[0032] The metallographic micrograph of the fine-grained zinc sheet prepared in this example is as follows: Figure 1 shown.

[0033] The XRD spectrum of the fine-crystalline zinc flakes prepared in this example is as follows Figure 2 shown.

[0034] The SEM-EBSD spectrum of the fine-grained zinc flakes prepared in this example is as follows: Figure 3 shown.

[0035] The battery using the fine-grained zinc sheet prepared in this embodiment was subjected to a cyclic voltammetry test. The test instrument was a Xinwei electrochemical workstation. The voltage range was set to 0.4-1.6V during the test. After two cycles of activation at 0.05A / g, the battery was cycled for 50 cycles at a current density of 0.5A / g. The test results are shown in FIG. Figure 4 shown.

[0036] The optical and scanning electron microscope images of the fine-grained zinc flakes after testing are shown in Figure 2. Figure 5 shown.

[0037] Comparative Example 1

[0038] The difference between this comparative example and Example 1 is that the zinc sheet used as the negative electrode of the zinc ion battery is an ordinary zinc sheet without annealing treatment and high-voltage torsion treatment, and the rest of the contents are the same as those described in Example 1.

[0039] The metallographic micrograph of the common zinc sheet used in this comparative example is also shown in FIG. Figure 1 shown.

[0040] The common zinc sheet in this comparative example was post-treated by the same means as in Example 1, and the treated zinc sheet was used as the negative electrode of the zinc ion battery. A button-type zinc ion battery was assembled by the same assembly means as in Example 1, and a cyclic voltammetry test was performed on the zinc ion battery by the same test method as in Example 1. The test results were also shown in FIG. Figure 4 shown.

[0041] Comparative Example 2

[0042] The difference between this comparative example and Example 1 is that the zinc sheet used as the negative electrode of the zinc ion battery is only subjected to annealing treatment and is not subjected to high-voltage torsion treatment. The rest of the contents are the same as those described in Example 1.

[0043] The metallographic micrograph of the annealed zinc sheet prepared in this comparative example is also shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the ordinary zinc sheet (a) of comparative example 1 of the present invention shows a non-uniform microstructure, the annealed zinc sheet (b) obtained by annealing without HPT treatment in comparative example 2 shows larger grains and regular grain boundaries, showing a relatively uniform microstructure, and the fine-grained zinc sheet (c) obtained by annealing first and then HPT treatment in Example 1 has significantly refined grains, the grains are refined into equiaxed grains, the grain boundaries are more complex, and the material shows obvious high strain characteristics; this shows that both annealing treatment and high pressure torsion (HPT) treatment can change the microstructure of the zinc sheet, and there is a synergistic effect between annealing treatment and high pressure torsion, which can more significantly refine the grains.

[0044] The XRD spectrum of the annealed zinc sheet prepared in this comparative example is also as shown Figure 2 As shown. Figure 2 It can be seen that the annealed zinc sheet (b) obtained by annealing without HPT treatment in Comparative Example 2 and the fine-grained zinc sheet (a) obtained by annealing first and then HPT treatment in Example 1 both have a hexagonal close-packed (HCP) structure consistent with PDF card number 03-065-3358, but the peak intensity of the (002) crystal plane in the fine-grained zinc sheet is significantly increased, indicating that the dual treatment of annealing and high-pressure torsion can make the zinc sheet grains present a (002) texture. The (002) crystal plane is considered to be the most stable and corrosion-resistant surface of zinc due to its relatively low surface energy, thus laying a theoretical foundation for the zinc sheet to overcome the defects of zinc dendrites, passivation and corrosion.

[0045] The SEM-EBSD spectrum of the annealed zinc sheet prepared in this comparative example is also as shown Figure 3 As shown. Figure 3It can be seen that the grain size of the annealed zinc sheet (a) obtained by annealing without HPT treatment in Comparative Example 2 is greater than 1000 μm, while the grain size of the fine-grained zinc sheet (b) obtained by annealing first and then HPT treatment in Example 1 is about 20 μm, indicating that high pressure torsion (HPT) treatment can further reduce the grain size of the zinc sheet, and the grain size of the zinc sheet can be reduced to a fine-grained level after annealing and high pressure torsion treatment.

[0046] The annealed zinc sheet obtained in this comparative example was post-treated by the same means as in Example 1, and the treated zinc sheet was used as the negative electrode of the zinc ion battery. A button-type zinc ion battery was assembled by the same assembly means as in Example 1, and a cyclic voltammetry test was performed on the zinc ion battery by the same test method as in Example 1. The test results were also shown in FIG. Figure 4 shown.

[0047] from Figure 4 It can be seen that at a current density of 0.5 A / g, the battery prepared by using the fine-crystalline zinc sheet obtained by annealing first and then HPT treatment in Example 1 as the negative electrode maintained a high discharge capacity of 520 mAh / g after 50 cycles, which was only slightly lower than its initial discharge capacity of 550 mAh / g, and the discharge capacity retention rate was 94.55%. Under the same conditions, the capacity of the battery prepared by using the ordinary zinc sheet without annealing and HPT treatment in Comparative Example 1 as the negative electrode decreased rapidly from 300 mAh / g to 117 mAh / g, and the capacity retention rate was only 39%; the capacity of the battery prepared by using the annealed zinc sheet obtained by annealing without HPT treatment in Comparative Example 2 as the negative electrode decreased rapidly from 400 mAh / g to 220 mAh / g, and the capacity retention rate is only 55%. It can be seen that both annealing and high-voltage torsion (HPT) treatments can improve the specific capacity and cycle performance of the battery, and the battery treated with annealing and high-voltage torsion (HPT) has a more excellent discharge specific capacity and better cycle performance, and can more effectively overcome the defects of passivation and corrosion of the zinc sheet, indicating that there is a synergistic effect between annealing and high-voltage torsion (HPT) treatments.

[0048] The optical and scanning electron microscope images of the annealed zinc sheet after testing are also shown in Figure 5 As shown. Figure 5 It can be seen that after 50 cycles of experiments, a large area of ​​local corrosion and mechanical damage areas were formed in the annealed zinc sheet obtained by annealing only without HPT treatment in Comparative Example 2, while the size and area fraction of the local corrosion and mechanical damage areas of the fine-crystalline zinc sheet obtained by annealing first and then HPT treatment in Example 1 were much smaller. It can be seen that the fine-crystalline zinc sheet obtained by annealing and high-voltage torsion (HPT) treatment has better chemical and mechanical stability when used as a negative electrode, and can effectively overcome the defects of zinc dendrites, passivation and corrosion of the zinc sheet.

[0049] Comparative Example 3

[0050] The only difference between this comparative example and Example 1 is that the zinc sheet used as the negative electrode of the zinc ion battery is only subjected to high-voltage torsion treatment, and is not subjected to annealing treatment before the high-voltage torsion treatment. The rest of the contents are the same as those described in Example 1.

[0051] The zinc sheet prepared in this comparative example was post-treated by the same means as in Example 1, and the treated zinc sheet was used as the negative electrode of the zinc ion battery. A button-type zinc ion battery was assembled by the same assembly means as in Example 1, and a cyclic voltammetry test was performed on the zinc ion battery by the same test method as in Example 1. The test results are shown in FIG. Figure 6 shown.

[0052] from Figure 4 It can be seen that at a current density of 0.5 a / g, the battery prepared by using the fine-crystalline zinc sheet obtained by annealing first and then HPT treatment in Example 1 as the negative electrode maintained a high discharge capacity of 520 mAh / g after 50 cycles, which was only slightly lower than its initial discharge capacity of 550 mAh / g, and the discharge capacity retention rate was 94.55%; the capacity of the battery prepared by using the ordinary zinc sheet without annealing and HPT treatment in Comparative Example 1 as the negative electrode dropped rapidly from 300 mAh / g to 117 mAh / g, and the capacity retention rate was only 39%; the capacity of the battery prepared by using the annealed zinc sheet obtained by annealing only without HPT treatment in Comparative Example 2 as the negative electrode dropped rapidly from 400 mAh / g to 220 mAh / g, and the capacity retention rate was only 55%;

[0053] from Figure 6 It can be seen that at a current density of 0.5 A / g, the capacity of the battery prepared by using the zinc sheet obtained by HPT treatment without annealing in Comparative Example 3 as the negative electrode decreased from 321 mAh / g to 290 mAh / g, and the capacity retention rate was 90%;

[0054] Therefore, in combination with Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Figure 4 and Figure 6 It can be seen that in the process of treating zinc sheets in the present invention, both annealing treatment and high-voltage torsion treatment can effectively improve the battery capacity, cycle stability and rate performance of the zinc negative electrode battery, and there is a synergistic effect between annealing treatment and high-voltage torsion treatment.

[0055] Comparative Example 4

[0056] The difference between this comparative example and Example 1 is that the zinc sheet used as the negative electrode of the zinc ion battery is first subjected to a high-voltage torsion treatment and then to an annealing treatment. The rest of the contents are the same as those described in Example 1.

[0057] The zinc sheet prepared in this comparative example was post-treated by the same means as in Example 1, and the treated zinc sheet was used as the negative electrode of the zinc ion battery. A button-type zinc ion battery was assembled by the same assembly means as in Example 1, and a cyclic voltammetry test was performed on the zinc ion battery by the same test method as in Example 1. The test results are shown in FIG. Figure 6 shown.

[0058] from Figure 4 It can be seen that at a current density of 0.5 a / g, the battery prepared by using the fine-crystalline zinc sheet obtained by annealing and then HPT treatment in Example 1 as the negative electrode maintained a high discharge capacity of 520 mAh / g after 50 cycles, which was only slightly lower than its initial discharge capacity of 550 mAh / g, and the discharge capacity retention rate was 94.55%; the capacity of the battery prepared by using the ordinary zinc sheet without annealing and HPT treatment in Comparative Example 1 as the negative electrode dropped rapidly from 300 mAh / g to 117 mAh / g, and the capacity retention rate was only 39%;

[0059] from Figure 6 It can be seen that at a current density of 0.5 A / g, the capacity of the battery prepared using the zinc sheet obtained by HPT followed by annealing in Comparative Example 4 as the negative electrode rapidly decreased from 297 mAh / g to 144 mAh / g, and the capacity retention rate was only 48%;

[0060] Therefore, in combination with Example 1, Comparative Example 1, Comparative Example 4 and Figure 4 and Figure 6 It can be seen that in the process of treating the zinc sheet of the present invention, the order of annealing treatment and high-pressure torsion treatment has a certain influence on the performance of the zinc sheet, and the order of annealing treatment and high-pressure torsion treatment is unchangeable.

[0061] Comparative Example 5

[0062] The only difference between this comparative example and Example 1 is that when the zinc sheet used as the negative electrode of the zinc ion battery is subjected to high-voltage torsion treatment, the pressure of the high-voltage torsion is 6 GPa, the rotation speed is 1 rpm, and the number of revolutions is 1 / 4 revolution. The rest of the contents are the same as those described in Example 1.

[0063] The zinc sheet prepared in this comparative example was post-treated by the same means as in Example 1, and the treated zinc sheet was used as the negative electrode of the zinc ion battery. A button-type zinc ion battery was assembled by the same assembly means as in Example 1, and a cyclic voltammetry test was performed on the zinc ion battery by the same test method as in Example 1. The test results are shown in FIG. Figure 6 shown.

[0064] from Figure 4It can be seen that at a current density of 0.5 A / g, the battery prepared by using the fine-crystalline zinc sheet obtained by annealing and then HPT treatment in Example 1 as the negative electrode maintained a high discharge capacity of 520 mAh / g after 50 cycles, which was only slightly lower than its initial discharge capacity of 550 mAh / g, and the discharge capacity retention rate was 94.55%; the capacity of the battery prepared by using the ordinary zinc sheet without annealing and HPT treatment in Comparative Example 1 as the negative electrode dropped rapidly from 300 mAh / g to 117 mAh / g, and the capacity retention rate was only 39%;

[0065] from Figure 6 It can be seen that at a current density of 0.5 a / g, the capacity of the battery prepared by using the zinc sheet obtained by annealing first and then HPT treatment and HPT treatment (1 / 4 turn) as the negative electrode in Comparative Example 5 decreased from 440 mAh / g to 387 mAh / g, and the capacity retention rate was 88%;

[0066] Therefore, in combination with Example 1, Comparative Example 1, Comparative Example 4 and Figure 4 and Figure 6 It can be seen that in the process of treating the zinc sheet in the present invention, the specific conditions used for annealing and high-pressure torsion treatment have a certain influence on the performance of the zinc sheet, and the specific conditions used for annealing and high-pressure torsion treatment are unpredictable.

[0067] Finally, it should be pointed out that the above are only some preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above contents of the present invention all fall within the scope of protection of the present invention.

Claims

1. A fine-grained zinc sheet with preferred orientation, characterized in that: It is obtained by successively subjecting zinc sheets to annealing treatment and high-pressure torsion treatment.

2. A method for preparing fine-crystalline zinc flakes with preferred orientation according to claim 1, characterized in that: The method comprises the following steps: a) annealing a clean zinc sheet at 520K to 530K for 1 to 1.5 hours to obtain an annealed zinc sheet; b) The annealed zinc sheet is subjected to a high-pressure torsion treatment, wherein the pressure of the high-pressure torsion is 5 to 10 GPa, the rotation speed is 1 to 2 rpm, and the number of revolutions is 9 to 11, so as to obtain a fine-grained zinc sheet with a preferred orientation.

3. A use of the fine-crystalline zinc sheet with preferred orientation according to claim 1 in an aqueous zinc ion battery, characterized in that: Used as the negative electrode of aqueous zinc-ion batteries.

4. The use according to claim 3, characterized in that: The upper and lower surfaces of the fine-crystalline zinc sheet are first polished to a thickness suitable for a negative electrode sheet of an aqueous zinc ion battery and then used as a negative electrode of the zinc ion battery.

5. The use according to claim 4, characterized in that: The upper and lower surfaces of the fine-crystalline zinc sheet are polished with sandpaper.

6. The use according to claim 4, characterized in that: The thickness of the fine-grained zinc sheet is ground to 0.5-0.7 mm.

7. An aqueous zinc ion battery, characterized in that: It includes a positive electrode and a negative electrode, a separator arranged between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is a VO2 positive electrode, the negative electrode is a fine-crystalline zinc sheet with preferential orientation as described in claim 1, the electrolyte is a 3M Zn(CF3SO3)2 aqueous solution, and the separator is glass fiber.

Citation Information

Cited By

  • Preparation method of zinc composite electrode and application of zinc composite electrode in aqueous zinc ion battery

    CN121748259A